Formation of spatial representations through perception, material models of geometric images - Ordashev T.Kh., Ордашев Т.Х. (Рroblems of engineering and professional education, 2023)
This article considers the problems of formation of geometrical ideas and the development of spatial thinking of students on the material of the course in descriptive geometry. In the solution of geometrical problems using different methods, but with the development of spatial thinking is more important will be the role of spatial models to the task. The use of models in solving tasks involves execution of a model in the material, drawing upon her solution plan, and its implementation, as the language models, and other means. Building a model - is a means of understanding the content of the problem. The training should be designed so that students moved from graphical solution of the task to her mental representation, object modeling as a means of implementing a primary analysis.